The social return of investment method as a tool for valuation and impact assessment for libraries - De Leon, Simon V.; Dorado, Dan Anthony D.; Apolinario, Rhea Rowena U.; Obille, Kathleen Lourdes B.; Golfo, Mary Grace, P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Social return on investment (SROI) is an impact assessment framework that measures changes and intangible social values used in both for-profit and non-profit types on institutions. The methods, as espoused by the Social Value International, consists of six procedural stages with seven guiding principles to facilitate discussions and maximize the impact of any activity.
This study sought to apply the SROI method as a tool for library evaluation and impact assessment through a case study with the Paraῆaque City Public Library (PCPL) to find out how and if the library can measure its social values using the SROI method, and what are the factors present that can raise the institutions' social values.
This research was done primarily from the 2018 annual report of the PCPL and includes data from users and staff that have used, or were involves with the library for the year 2018. The data gathering methods used were questionnaires, and interviews, and data were analyzed using a mixed method of quantitative and qualitative analysis.
The following activities and functions of the PCPL were included: reader of library services, internship and immersion program, computer literacy program, health and wellness program, and the children's daycare services.
Results of the study concluded that the SROI method can indeed be used to a library setting and is applicable as a valuation and impact assessment tool. The resulting total SROI ratio of PCPL is 1:1.12, meaning that for every PhP 1.00 invested, the library creates PhP 1.12 in social values. The outcome that created the most social value for the library users stakeholders are the answers "help to work, career, studies and or increased productivity," followed by "entertained and relaxed" and the felt more socially inclusive and or feeling of belongingness. For the library staff, the outcome that created the most social value is "increased self-esteem".
Overall, this study proved that the SROI method can greatly assist the library in determining the value of their library programs and activities and would enable them to have better programming in their strategic objectives and goals.
Thesis (Master of Library and Information Science)